Japanese environmental policy and mobilization for environmental protection of industries (2016)
This article addresses the issue of the environment from the perspective of Japan; a country that has faced difficult environmental situations, but that today is consolidated as a country capable of configuring sustainable strategies for the present and future of the world population. This article analyzes the environmental policies promoted by the Japanese government, which have generated a high impact, both for its citizens and for national industries. In turn, two Japanese multinationals are exposed, which have implemented multiple campaigns and tactics to promote the protection and preservation of the environment. Finally, there is a reflection on how Japan, a country with a high technological, economic and social development, has been able to carry out an environmental project of such magnitude that it has become the least polluting country in the world, an aspect that should serve as example to the international community.